A combination of polarity reversal, Diels–Alder cycloaddition and skeletal remodeling to access pyridine-fused nitrones. Issue 30 (28th March 2022) - Han, Huabin; Li, Chaoyang; Niu, Xinyue; Wang, Yuxia; Zhang, Wenjing; Wang, Qilin
Abstract : An unprecedented cascade strategy consisting of piperidine-promoted polarity reversal, normal electron-demand Diels–Alder cycloaddition and skeletal remodeling was developed to construct structurally novel pyridine-fused nitrones in up to 82% yield. Abstract : An unprecedented cascade strategy consisting of polarity reversal, normal electron-demand Diels–Alder cycloaddition and skeletal remodeling was developed to construct novel pyridine-fused nitrones in up to 82% yield. The key to the success was the umpolung process, which transformed the electron-deficient 3-nitropyridinium ring into a reactive, π-extended cyclic nitroalkene, serving as a rarely reported hetero-diene to participate in normal Diels–Alder cycloadditions.